Investigating the role of bentonite clay with different soil amendments to minimize the bioaccumulation of heavy metals in Solanum melongena L. under the irrigation of tannery wastewater - Khan, Waqas ud Din; Wei, Xiangying; Ali, Hafiz Haider; Zulfiqar, Faisal; Chen, Jianjun; Iqbal, Rashid; Zaheer, Muhammad Saqlain; Ali, Basharat; Ghafoor, Sana; Rabiya, Umm e.; Waqas, Muhammad; Ghaffar, Rabia; et al. (Frontiers in Plant Science, 2022)
Tanneries wastewater is a major source of chromium (Cr) stress in soil and plants when used for crop irrigation, with unavoidable toxicological effects minimized through two independent steps in the present study. In the first step, a batch sorption experiment was conducted in which Cr was adsorbed through bentonite clay and DTPA extraction method was used to analyze chromium concentration in the soil after regular time intervals (30, 60, 12, 360, 480, 540, 630, 690, and 1218 min) which reduced chromium concentration from 38.542 mgL-1 for 30 min to 5.6597 mgL-1 for 20.3 hr, respectively, by applying 1% bentonite. Hence, it was concluded that an increase in the time allowed soil adsorbent to adsorb maximum chromium from soil samples. In the second step, a pot experiment was conducted with 10 different treatments to improve the physiological and biochemical parameters of the Solanum melongena L. plant under tanneries wastewater stress. There were four replicates and the crop was harvested after 20 days of germination. It was investigated that the application of wastewater significantly (P < 0.01) reduced growth of Solanum melongena L. plant by reducing root (77%) and shoot (63%) fresh weight when compared with CFOP (Ce-doped Fe2O3 nanoparticles); while, chlorophyll a and b (4-folds) were improved under CFOP application relative to control. However, the deleterious effects of Cr (86%) and Pb (90%) were significantly decreased in shoot through CFOP application relative to control. Moreover, oxidative damage induced by the tannery’s wastewater stress significantly (P < 0.01) tolerated by the BN, BT, FOP and CFOP. However, results were well pronounced with the application of CFOP which competitively decreased the concentrations of MDA (95%), H2O2 (89%) and CMP (85%) by efficiently triggering the activities of antioxidant defense mechanisms such as APX (3-folds), CAT (2-folds) and phenolics (75%) in stem relative to control. Consequently, all the applied amendments (BN, BT, FOP and CFOP) were efficiently performed to tolerate the tannery’s wastewater stress; results were more pronounced with the addition of CFOP and FOP + BT to improve physiological and biochemical parameters of Solanum melongena L. plant in an eco-friendly way.